Come and read: interpretive approaches to the Gospel of John - Myers, Alicia D.; Jodrey, Lindsey S. (Interpreting Johannine literature, 2020)
Come and read : hermeneutics and interpretive perspectives in the Gospel of John / Alicia D. Myers and Lindsey S. Jodrey -- part 1 : John 1:1-18 : narrative, sociocultural, intertextual, and rhetorical readings. Beginnings : introducing the narrative of the word though the prologue of John's Gospel / Sherri Brown -- John 1 beyond the binary / Lindsey S. Jodrey -- Revealing the fuller Word / Craig S. Keener -- Ambiguity as a rhetorical strategy in the prologue to John's Gospel / Jo-Ann A. Brant -- part 2 : John 10 : narrative, sociocultural, intertextual, and rhetorical readings. The parable of the sheepfold : a narrative reading of John 10 / Dorothy A. Lee -- Jesus the Good Shepherd : John 10 as political rhetoric / Warren Carter -- Persuasion through allusion : evocations of "shepherd(s)" and their rhetorical impact in John 10 / Catrin H. Williams -- Discerning characters : parrēsia, paroimia, and Jesus's rhetoric in John 10:1-21 / Alicia D. Myers -- part 3 : John 20 : narrative, socioclutural intertextual, and rhetorical readings. Narrative-critical interpretation of John 20 / Craig R. Koester -- Reading Mary Magdalene with Stacey Abrams : developing an inclusive national consciousness / Angela N. Parker -- Recognition and "those who have not seen" : John's reception of synoptic resurrection narratives / Helen K. Bond -- Rhetorical vividness in John 20 : making Jesus present before the eyes / Kasper Bro Larsen.